2023
DOI: 10.3390/proteomes11020014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Saliva Proteome of Pigs with Diarrhoea Caused by Escherichia coli

Abstract: Escherichia coli represents the main cause of diarrhoea in pigs. Saliva can provide information about the pathophysiology of diseases and be a source of biomarkers. We aimed to identify changes in the salivary proteome of pigs with diarrhoea caused by E. coli. Saliva samples were collected from 10 pigs with this disease and 10 matched healthy controls. SDS-PAGE (1DE) and two-dimensional gel electrophoresis (2DE) were performed, and significantly different protein bands and spots were identified by mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In the present study, the mean increase of ITIH4 was 2.87-fold, in line with the magnitude of increases reported in the serum of pigs with E. coli infection compared to healthy pigs [ 42 ]. The activity of ADA showed an increase in pigs with diarrhea in our study, in line with a previous report [ 20 ] in which increments in this protein in saliva were detected by proteomics and a spectrophotometric assay in pigs with the same disease. The increase of alpha-amylase in this report could be due to the described role of an increase in salivary alpha-amylase as an evolutive adaptation in order to protect the organism against gastrointestinal pathogens [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the mean increase of ITIH4 was 2.87-fold, in line with the magnitude of increases reported in the serum of pigs with E. coli infection compared to healthy pigs [ 42 ]. The activity of ADA showed an increase in pigs with diarrhea in our study, in line with a previous report [ 20 ] in which increments in this protein in saliva were detected by proteomics and a spectrophotometric assay in pigs with the same disease. The increase of alpha-amylase in this report could be due to the described role of an increase in salivary alpha-amylase as an evolutive adaptation in order to protect the organism against gastrointestinal pathogens [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of ETEC in the swine industry severely impacts the well-being of pigs and the economic sustainability of the sector [ 19 ]. A previous proteomic study on saliva investigated the variations of salivary proteins in pigs suffering from diarrhea due to E. coli [ 20 ]. In this study, several proteins were identified that varied in diseased pigs compared with healthy pigs, among them there were proteins related to the immune system like adenosine deaminase (ADA).…”
Section: Introductionmentioning
confidence: 99%